2013
DOI: 10.1113/jphysiol.2012.247288
|View full text |Cite
|
Sign up to set email alerts
|

‘Eventless’ InsP3‐dependent SR‐Ca2+ release affecting atrial Ca2+ sparks

Abstract: Key points• Inositol 1,4,5-trisphosphate receptors (InsP 3 Rs) are functionally expressed in cardiac myocytes.• The influence of inositol 1,4,5-trisphosphate-induced sarcoplasmic reticulum (SR)-Ca 2+ release (IP3ICR) on atrial excitation-contraction coupling (ECC) under physiological and pathophysiological conditions remains elusive.• The present study focuses on local IP3ICR and its functional consequences for ryanodine receptor (RyR) activity and subsequent Ca 2+ -induced Ca 2+ release in atrial myocytes.• H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 39 publications
(68 reference statements)
5
17
0
Order By: Relevance
“…It also occurs in the ER of rat sensory neurons (Solovyova and Verkhratsky, 2003) and in mammalian skeletal muscle RyRs and IP 3 Rs cooperate to activate Ca 2+ -signaling via the SR (Tjondrokoesoemo et al , 2013). A similar cooperativity has been detected in atrial cells of the heart (Horn et al , 2013). …”
Section: Intracellular Calcium Channels In Ciliatessupporting
confidence: 77%
See 1 more Smart Citation
“…It also occurs in the ER of rat sensory neurons (Solovyova and Verkhratsky, 2003) and in mammalian skeletal muscle RyRs and IP 3 Rs cooperate to activate Ca 2+ -signaling via the SR (Tjondrokoesoemo et al , 2013). A similar cooperativity has been detected in atrial cells of the heart (Horn et al , 2013). …”
Section: Intracellular Calcium Channels In Ciliatessupporting
confidence: 77%
“…Pt CRC-II/IP 3 Rs are restricted to the contractile vacuole complex (serving in fresh water organisms for the expulsion of water and of some ions, including an excess of Ca 2+ ) and, therefore, may fine-tune Ca 2+ homeostasis by partial reflux of Ca 2+ (Ladenburger et al , 2006). Spontaneous Ca 2+ puffs are seen along the tubular extensions of this organelle, indicating constitutively active IP 3 R type channels - a phenomenon reported later on also for a chicken lymphocyte cell line (Cardenas et al , 2010) and mammalian atrial myocytes (Horn et al , 2013). Pt CRC-III molecules are associated with recycling vesicles engaged in phagosome formation (Ladenburger and Plattner, 2011).…”
Section: Intracellular Calcium Channels In Ciliatessupporting
confidence: 60%
“…Crosstalk between IP 3 Rs and RyRs, in which activation of IP 3 Rs via elevated IP 3 leads to recruitment of neighbouring RyRs receptors, leading to larger Ca 2+ release, was first suggested in smooth muscle cells [10]. Similar interaction between IP 3 Rs and RyRs has also been proposed in embryonic myocytes [11,12], atrial cardiac myocytes [13][14][15], spontaneously hypertensive rat (SHR) myocytes [8], and rabbit ventricular myocytes [16]. Given the lower abundance and Ca 2+ flux of IP 3 Rs relative to RyRs, how they can affect ECC remains poorly understood.…”
Section: Introductionmentioning
confidence: 78%
“…To test the role that IP 3 Rs play in spark activation, we next considered which dyad trigger settings were sufficient to generate a spark. Experiments on cardiac and smooth muscle cells suggested that IP 3 Rs may not create a spark by themselves, but can facilitate neighbouring RyR opening [10,12,13]. Therefore we tested how one dyad will behave when: (a) no initiation is applied; (b) 5 IP 3 Rs are opened at t = 0 ms; (c) 5 Simulation results shown in Fig.…”
Section: Ip 3 Rs Can Facilitate Spark Initiationmentioning
confidence: 99%
“…In cardiomyocytes, particularly in atrial cells where IP 3 Rs are more abundant, a modulatory function of IP 3 Rs on CICR has been recognized (Mackenzie et al 2002). IP 3 Rs may indeed participate in Ca 2+ signalling, secondary to acute or chronic stimulation of membrane receptors linked to the phospholipase C (PLC)-IP 3 signalling pathways, such as endothelin (ET) or angiotensin (AT) II receptors (Horn et al 2013). Recently, it has been found that IP 3 Rs located in the nuclear envelope are involved in excitation-transcription coupling, thereby participating in the control of gene expression programmes.…”
mentioning
confidence: 99%